GOVERNANÇA CORPORATIVA E A GESTÃO DE PESSOAS : ESTUDO DE CASO EM UMA ORGANIZAÇÃO DE SEGUROS - Pereira, Carmen Silvia (2004)
The current study discusses aspects related to good practices in corporate governance in a Brazilian company in the insurance, health and pension business, comprehending the issue on the relationship between the principal instrument of governance the administrative council and it s stakeholders: the person, here known as the company s managers and employees. Through a case study, three researches are presented, evaluated and compared: the first, accomplished in 2001 by the association of two big consulting companies, about the corporate governance stage in 53 big Brazilian companies; the second, accomplished by the author of this thesis with some counselors of the company presented as object of this case study to evaluate, qualitatively the governance model adopted, comparing with the consulting study. The third research refers to a organizational climate study concluded in 2003 at the researched company, contracted to a specialized consulting. Next is done a qualitative analysis of the three researches results, concluding that the corporate governance model model of the researched company can be classified as an emergent model , although it was verified that the model development doesn t reach all the stakeholders, once the climate research detected some hiatus between the governance practices and the correspondent perception of the managers and employees.